2016
DOI: 10.1007/s10753-016-0353-z
|View full text |Cite
|
Sign up to set email alerts
|

Paeonol Inhibits Lipopolysaccharide-Induced HMGB1 Translocation from the Nucleus to the Cytoplasm in RAW264.7 Cells

Abstract: Transport of high-mobility group box 1 (HMGB1), a highly conserved non-histone DNA-binding protein, from the nucleus to the cytoplasm is induced by lipopolysaccharide (LPS). Secretion of HMGB1 appears to be a key lethal factor in sepsis, so it is considered to be a therapeutic target. Previous studies have suggested that paeonol (2'-hydroxy-4'-methoxyacetophenone), an active compound of Paeonia lactiflora Pallas, exerts anti-inflammatory effects. However, the effect of paeonol on HMGB1 is unknown. Here, we inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…It has been confirmed that paeonol inhibits the production of proinflammatory cytokines (TNF-α and IL-1β) and affects the translocation and secretion of the late inflammatory factor HMGB1 42 . The nuclear protein HMGB1 is a late-stage lethal inflammatory factor that is translocated to the extracellular space as a signal for the spread of inflammation 16,43,44 .…”
Section: Discussionmentioning
confidence: 92%
“…It has been confirmed that paeonol inhibits the production of proinflammatory cytokines (TNF-α and IL-1β) and affects the translocation and secretion of the late inflammatory factor HMGB1 42 . The nuclear protein HMGB1 is a late-stage lethal inflammatory factor that is translocated to the extracellular space as a signal for the spread of inflammation 16,43,44 .…”
Section: Discussionmentioning
confidence: 92%
“…Paeonol suppresses inflammatory cytokines in LPS-induced macrophage cells and protects mice from lethal endotoxin shock by regulating the production of tumor necrosis factor- α (TNF- α ), IL-1 β , interleukin-6 (IL-6), and interleukin-10 (IL-10) via inactivation of I κ B α , ERK1/2, JNK, and p38 MAPK [ 27 , 36 ]. Furthermore, paeonol also reduces the nucleocytoplasmic transportation of extracellular high mobility group box 1 (HMGB1) by upregulating histone deacetylase 3 (HDAC3) [ 38 , 39 ]. It is worth noting that the anti-inflammatory and antioxidative activities of paeonol and its metabolites were found mostly through blocking MAPK/ERK/p38 signaling pathway and PI3K/Akt/NF- κ B pathway [ 27 , 40 , 41 ].…”
Section: Immunomodulatory Effect Of Cynanchum Paniculatumentioning
confidence: 99%
“…Paeonol found in Paeonia suffruticosa (moutan cortex) can suppress LPS-induced HMGB1 translocation from the nucleus to the cytoplasm in RAW264.7 cells [235,236]. It (60-120 µM) can attenuate aging of MRC-5 cells and inhibit EMT of HaCaT cells induced by aging MRC-5 cell-conditioned medium [237].…”
Section: Reversal Of Emt By Anti-inflammatory Natural Compoundsmentioning
confidence: 99%